2021
DOI: 10.3390/ijms22189927
|View full text |Cite
|
Sign up to set email alerts
|

Fenton-Chemistry-Based Oxidative Modification of Proteins Reflects Their Conformation

Abstract: In order to understand protein structure to a sufficient extent for, e.g., drug discovery, no single technique can provide satisfactory information on both the lowest-energy conformation and on dynamic changes over time (the ‘four-dimensional’ protein structure). Instead, a combination of complementary techniques is required. Mass spectrometry methods have shown promise in addressing protein dynamics, but often rely on the use of high-end commercial or custom instruments. Here, we apply well-established chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…However, such organic consumption would reduce the degradation efficiency of diesels by competing with •OH. In addition, the intensity magnification of tyrosine-like protein after FT treatment may be ascribed to the hydrolysis of macromolecular proteins . On the other hand, after BP treatment, the content of FAL and protein-like substances (including tyrosine-like and tryptophan-like proteins) in BPS decreased, which was attributed to these substances having high reactivity in oxidation .…”
Section: Resultsmentioning
confidence: 97%
“…However, such organic consumption would reduce the degradation efficiency of diesels by competing with •OH. In addition, the intensity magnification of tyrosine-like protein after FT treatment may be ascribed to the hydrolysis of macromolecular proteins . On the other hand, after BP treatment, the content of FAL and protein-like substances (including tyrosine-like and tryptophan-like proteins) in BPS decreased, which was attributed to these substances having high reactivity in oxidation .…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, oxidizing 96 samples one by one using Fe­(II)-EDTA/H 2 O 2 /ascorbate (e.g., ref ) would take hours. This length of time exceeds the stability of the Fe­(II)-EDTA reagent (Figure S1I) and that of ascorbate and likely the endurance of all but the hardiest scientist. (iii) We have demonstrated that chemical generation of • OH is compatible with a range of solutes and conditions commonly used to analyze proteins (Figure S1).…”
Section: Discussionmentioning
confidence: 94%
“…That Fenton-generated • OH can be used for protein oxidative footprinting has been demonstrated. These studies utilized the Tullius nucleic acid analysis approach of adding Fe­(II)-EDTA, H 2 O 2 , and ascorbate to generate • OH in samples. While nucleic acid oxidative footprinting studies are typically conducted using a single radical dose, the importance of dose-dependent oxidation to protein analysis is well established. , We found that the Fe­(II)-EDTA/H 2 O 2 /ascorbate cocktail does not support the reproducible dose-dependent generation of • OH required for reliable protein analysis.…”
mentioning
confidence: 99%
“…Fits of the reaction profile using zeroth, first and second order kinetics (Figure S17; Figure S16; Figure S18). Ref [ 11 , 17 , 22 , 26 , 27 , 28 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%